الصحة النفسية لدى أمهات المعاقين عقليا في ضوء بعض المتغيرات - شطي، الشيماء, خيشة، العطرة (جامعة الوادي university of Eloued, 2020)
ملخص تعالج الدراسة الحالية موضوع الصحة النفسية لدى أمهات المعاقين عقليا، بالمركز النفسي البيداغوجي للمعاقين عقليا بولاية الوادي خلال الموسم 2019/2020. تهدف هذه الدراسة إلى معرفة مستوى الصحة النفسية لدى أمهات المعاقين عقليا بالمركز النفسي البيداغوجي بالوادي، ولتحقيق الهدف المرجو اعتمدت الدراسة على المنهج الوصفي الذي يتناسب مع طبيعة الدراسة. كان من المفترض أن تعتمد الدراسة على عينة قوامها(60) أم من أمهات المعاقين عقليا، والتي يفترض أن يتم اختيارهم بطريقة عشوائية بسيطة، وكذلك من المفترض أن يتم جمع البيانات من خلال الاعتماد على استمارة البيانات الأولية والتي تشتمل على بيانات عن جنس المعاق وبيانات عن المستوى التعليمي للأم، وكذلك بيانات عن عمر المعاق، وبيانات عن درجة الإعاقة. وكذلك مقياس الصحة النفسية الذي أعده صلاح فؤاد محمد مكاوي لقياس الصحة النفسية لأمهات المعاقين عقليا بمعهد فرسان الإدارة. ونظرا لإلغاء الفصل التطبيقي والإكتفاء بإعطاء تصور حول الدراسة الميدانية، وكذلك إلغاء فصل النتائج فقد تعذر علينا جمع البيانات وقد افترضنا أن تكون النتائج المتوصل إليها كالآتي: - توجد فروق ذات دلالة إحصائية في الصحة النفسية لدى أمهات المعاقين عقليا حسب جنس المعاق. - توجد فروق ذات دلالة إحصائية في الصحة النفسية لدى أمهات المعاقين عقليا حسب عمر المعاق. - توجد فروق ذات دلالة إحصائية في الصحة النفسية لدى أمهات المعاقين عقليا حسب المستوى التعليمي للأم. - توجد فروق ذات دلالة إحصائية في الصحة النفسية لدى أمهات المعاقين عقليا حسب درجة الإعاقة. Summary The current study deals with the issue of mental health among mothers of the mentally handicapped, at the Educational Psychological Center for the Mentally Handicapped in the state of EL-oued during the season 2019/2020. This study aims to know the level of mental health of the mothers of the mentally handicapped in the pedagogical psychological center in the valley, and to achieve the desired goal, the study relied on the descriptive approach that is commensurate with the nature of the study. The study was supposed to be based on a sample of (60) mothers from the mothers of the mentally handicapped, who were supposed to have been chosen in a simple random way, and it is also assumed that the data were collected by relying on the primary data form, which includes data on the gender of the disabled and data, On the mother’s educational level, as well as data on the age of the disabled, and data on the degree of disability. As well as the mental health scale prepared by Salah Fouad Mohamed Makkawi to measure the mental health of mothers of the mentally handicapped at the Knights of Administration Institute. Given the abolition of the applied separation and only giving a perception about the field study, as well as the abolition of the separation of the results, we were unable to collect data and we assumed that the findings were as follows: - There are statistically significant differences in the mental health of mothers with mental disabilities according to the gender of the disabled. - There are statistically significant differences in the mental health of mothers with mental disabilities according to the age of the disabled. - There are statistically significant differences in the mental health of mothers with mental disabilities according to the educational level of the mother. - There are statistically significant differences in the mental health of mothers with mental disabilities according to the degree of disability.
دراسة وصفية على عينة من أمهات المعاقين عقليا بالمركز النفسيي
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: الصحة النفسية، أسر المعاقين عقليا، الإعاقة العقلية; Santé mentale, familles de handicapés mentaux, handicap mental; Mental health, families of the mentally handicapped, mental disability